Irenaeus on the Christian faith a condensation of Against heresies - Irenaeus, Saint, Bishop of Lyon.; Payton, James R., 1947- (Cambridge, U.K. : James Clarke & Co., 2012)
Annotation With this distillation readers now have access to Irenaeus' rich presentation of the Christian faith, saturated in a thorough knowledge of Scripture and steadfastly rooted in the apostolic tradition of the early church. For anyone who wants to know what the early Christian church had received and passed on from the apostles.
Frontcover; Title; Contents; Preface; Acknowledgments; Abbreviations; Introduction; The Life of Irenaeus; Opposing Gnosticism; The General Gnostic Pattern; Gnostic Christianity; Irenaeus ' Presentation of Christianity; Unity and Coherence; One Lord, One Faith, One History; Recapitulation; Significance of Against Heresies; First in a Long Line; An Audacious but Unanswered Claim; Irenaeus and "Normative" Christianity; Structure of Against Heresies; Book 1; Book 2; Book 3; Book 4; Book 5; Bibliography; Back cover.
Master record variable field(s) change: 072
Keywords: Gnosticism -- Early works to 1800.; Theology, Doctrinal -- Early works to 1800.; Apologetics -- Early works to 1800.; RELIGION -- Christianity -- Catechisms; Apologetics; Gnosticism; Theology, Doctrinal; RELIGION / History; Electronic books; Early works